2011
DOI: 10.1038/jp.2011.157
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled, prospective study of bosentan for the treatment of persistent pulmonary hypertension of the newborn

Abstract: Objective: To assess the efficacy and safety of bosentan as an adjuvant therapy of persistent pulmonary hypertension of the newborn (PPHN).Study Design: Forty-seven neonates with PPHN were randomly assigned to receive either bosentan (n ¼ 24) or placebo (n ¼ 23). Efficacy was evaluated with a favorable outcome defined as fulfilling all the following criteria (for example, oxygenation index <15, normal pulmonary artery pressure (<20 mm Hg) and no premature discontinuation of the drug because of drug-related tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 20 publications
3
53
0
Order By: Relevance
“…These agents have been used successfully in treating PPHN in neonates with and without CDH [44,45]. The effects of treatment may be best addressed by repeated cardiac evaluation [46].…”
Section: Resultsmentioning
confidence: 99%
“…These agents have been used successfully in treating PPHN in neonates with and without CDH [44,45]. The effects of treatment may be best addressed by repeated cardiac evaluation [46].…”
Section: Resultsmentioning
confidence: 99%
“…Two recent trials have shown that bosentan is well tolerated in neonates with PPHN. One single-center trial reported that bosentan led to substantial improvements in oxygenation in an iNO-naïve population of PPHN infants [67], but a subsequent multicenter trial (FUTURE-4) found that bosentan as adjunctive therapy for iNO did not improve PPHN outcomes, time on iNO or time to extubation, due possibly in part to inconsistent intestinal absorption [68]. …”
Section: Other Pulmonary Vasodilatorsmentioning
confidence: 99%
“…75 Still, clinical studies with the nonselective ET-1 receptor blocker bosentan have showed promising results and demonstrate their therapeutic potential in adults 76,77 and possibly newborns. 78 Ductal ligation and chronic hypoxia both enhance ET-1-mediated pulmonary vascular contraction in sheep. Ivy et al 79 showed that in the ovine fetus, ductal ligation increased ET-1 content 3-fold, while ET-1 receptor activity was altered to promote vasoconstriction.…”
Section: Hypoxia-induced Pulmonary Vasoconstriction (Hpv)mentioning
confidence: 98%